2010
DOI: 10.1016/j.cub.2010.09.007
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Aux/IAA28 Signaling Cascade Activates GATA23-Dependent Specification of Lateral Root Founder Cell Identity

Abstract: We have identified the first molecular components that control lateral root founder cell identity in the Arabidopsis root. These include an IAA28-dependent auxin signaling module in the basal meristem region that regulates GATA23 expression and thereby lateral root founder cell specification and root branching patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
501
0
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 434 publications
(518 citation statements)
references
References 36 publications
8
501
0
9
Order By: Relevance
“…We observed that factors regulating auxin signaling, such as SOLITARY ROOT (IAA14), could be also involved in de novo root initiation; we detected decreased root capacity for slr-1, which could be indicative of fewer primordia initiation. In addition, the IAA28 module, which is upstream of lateral root founder cell specification (De Rybel et al, 2010), also regulates de novo root founder cell specification or initiation, although further experiments could dissect more precisely at which stage IAA28 is involved. Our results show that factors primarily involved in formation of lateral roots are also affected in rooting of leaves, suggesting the existence of partially overlapping auxin signaling modules during postembryonic root development.…”
Section: Root Primordia Initiation and Patterningmentioning
confidence: 99%
“…We observed that factors regulating auxin signaling, such as SOLITARY ROOT (IAA14), could be also involved in de novo root initiation; we detected decreased root capacity for slr-1, which could be indicative of fewer primordia initiation. In addition, the IAA28 module, which is upstream of lateral root founder cell specification (De Rybel et al, 2010), also regulates de novo root founder cell specification or initiation, although further experiments could dissect more precisely at which stage IAA28 is involved. Our results show that factors primarily involved in formation of lateral roots are also affected in rooting of leaves, suggesting the existence of partially overlapping auxin signaling modules during postembryonic root development.…”
Section: Root Primordia Initiation and Patterningmentioning
confidence: 99%
“…1D and 2C). The altered root pattern could originate at the level of lateral root founder cell specification, which occurs in the basal meristem before the initial anticlinal division of the founder cells (De Rybel et al, 2010). To visualize the effect of c-CA on lateral root priming, we used a reporter line harboring the promoter of the GATA23 transcription factor fused to a GUS reporter.…”
Section: Ca Affects Plant Developmentmentioning
confidence: 99%
“…To visualize the effect of c-CA on lateral root priming, we used a reporter line harboring the promoter of the GATA23 transcription factor fused to a GUS reporter. GATA23 expression is considered as hallmark of the earliest steps in lateral root formation (De Rybel et al, 2010). In mock-treated plants, GUS expression was observed in pericycle cells starting close to the root tip and continued along the root in a zone lacking emerged lateral root primordia.…”
Section: Ca Affects Plant Developmentmentioning
confidence: 99%
See 2 more Smart Citations